(untitled) (Contemporary Journal of Social Science Review, 2025)
Purpose: The study highlights the urgent need for organizational interventions focusing on leadership development and wellbeing promotion to mitigate toxicity’s detrimental impacts. This study addresses the pervasive issue of toxic leadership within Pakistan’s telecommunications sector, where destructive leader behaviors such as abusive supervision, authoritarianism, narcissism, and unpredictability have been documented to negatively impact employee mental health and organizational performance. Objective: The primary objectives are to investigate the direct effects of toxic leadership on employee performance and mental health and to examine the mediating role of psychological wellbeing in mitigating these adverse outcomes. Design/Methodology: Employing a quantitative, cross-sectional survey design, data were collected from 350 full-time employees, with a representative sample in terms of gender, education level, and age. Validated instruments measured toxic leadership, employee performance, task and organizational citizenship behaviors, psychological wellbeing, and mental health symptoms using established scales. Findings: The findings confirm that toxic leadership substantially depletes employee psychological resources, undermining mental health and reducing performance, whereas psychological wellbeing acts as a protective buffer fostering resilience and productivity. Overall, the research contributes important empirical evidence to leadership and organizational psychology literature in developing country contexts, offering actionable insights for human resource practitioners and policymakers aiming to enhance workforce wellbeing and effectiveness in Pakistan’s private sector